Pushkin Death of a Poet - Vickery, Walter N. (Indiana University Press, 1968)
Pushkin: Death of a Poet is a careful appraisal of the available facts, casting doubt on many sidely circulated theories concerning Pushkin's death. Sifting the evidence from contemporary letters, diaries, and other sources, the author examines Pushkin's motives: his intense envy of his wife's popularity; his own social discomfort and failure; his humiliating obligation to the Tsar; his growing artistic sterility. He recreates the personalities of the central figures in the story and explores the tangled web of events which preceded the duel and the desperate last-minute efforts by friends of both Pushkin and d'Anthés to prevent their meeting. A vivid account of the duel itself and its tragic aftermath concludes this engrossing study of a perplexing chapter in literary history.